An Anthropological Perspective of Power Dynamics and Conflicts in Smallholder Plantation Agriculture in Africa: The Case of Mbandjock, Cameroon - Clement, BONUH CHE; TIKERE MOFFOR, Exodus (Technium Sustainability, 2025)
This article investigates the power dynamics and conflicts arising in smallholder plantation agriculture in Mbandjock, Cameroon. Smallholder plantations agriculture everywhere in the world including Mbandjock help to ensure food security. The smallholder plantations agriculture in Mbandjock, Cameroon, have seen significant growth, yet the emerging power dynamics and conflicts within this sector have received little attention. The questions are; What are the perceptions of stakeholders in smallholder plantations agriculture in Mbandjock? What are the changes which are currently going on in smallholder plantations agriculture in Mbandjock? What are the causes of conflict in these smallholder plantations in Mbandjock? The study seeks to examine; the perceptions, attitudes, and behaviours of stakeholders involved in the emerging plantations in the region, the changes which are taking place in these smallholder plantations, and the sources of conflicts in the smallholder plantations. The research was purely qualitative in which we used methods such as observation, interviews and photography to collect data. This data was analysed using content analysis and interpreted using the theories of cultural dynamics of Balandier and the conflict of Marx. Major findings reveal that smallholder plantations have brought about new power dynamics across political, spiritual, economic, and social spheres, leading to significant lifestyle changes. Land grabbing has occurred under two distinct land tenure laws; customary and state laws, resulting in conflicts between the indigenes and administrative, political, and traditional authorities. This study highlights the complex interplay between power dynamics and conflicts within smallholder plantation agriculture in Mbandjock, Cameroon. It emphasizes the necessity for further research and policy interventions to address these challenges.